Exploring the Potential of Carboxymethyl Chitosan and Oxidized Agarose to Form Self-Healing Injectable Hydrogels - Eduard A. Córdoba; Natalia A. Agudelo; Luis F. Giraldo; Claudia E. Echeverri-Cuartas (Polysaccharides, 2025)
Localized treatment has emerged as an excellent alternative to minimize the side effects associated with the systemic dispersion of therapeutic agents, which can damage healthy tissues. Injectable hydrogels offer a promising solution because they can encapsulate and release therapeutic agents in a controlled manner. In this context, this study focuses on the development and characterization of an injectable hydrogel based on carboxymethyl chitosan (CMCh) and oxidized agarose (OA), in which chemical crosslinking through imine bond formation avoids the use of external crosslinking agents. Several polymer ratios were evaluated to obtain hydrogels (OA:CMCh), and stable gels were formed at physiological temperatures in all cases. The hydrogels were injectable through a 21 G needle with forces below 30 N, formed porous structures, and exhibited a self-healing capacity after 48 h. Additionally, the hydrogels displayed compressive strengths ranging from 26 to 71 kPa and elastic moduli similar to those of human tissues (6–20 kPa). Swelling percentages of up to 3090% were achieved owing to the high hydrophilicity of CMCh and OA, and strong chemical crosslinking maintained the gel stability for two weeks with low mass loss rates (<21%). Furthermore, polymer ratio variation and storage at 4 °C were observed to affect the hydrogel characteristics, allowing for property modulation according to the application needs. These results indicate that the proposed polymeric combination enables the formation of hydrogels with the potential for localized drug delivery.